Identification of AFLP markers linked with low-temperature resistance in introgressions transferred from Festuca arundinacea to Lolium multiflorum. - Pawlowicz, Izabela; Rapacz, Marcin; Bocianowski, Jan (Plant Breeding and Seed Science, 2008)
BC3-152/53 population of L. multiflorum plants comprising single introgression of F. arundinacea genome was tested for low-temperature tolerance. 13.8% of individuals were more freezing-resistant, whereas 16.25% had higher winter hardiness than control L. multiflorum plants. AFLP analysis were performed resulting in generation of 19 markers linked with freezing resistance, 7 linked with winter hardiness and 2 markers correlated with both traits. It indicates that Festuca introgression could make the impact on Lolium stress resistance...